The marginal rocks of the Rustenburg Layered Suite of the Bushveld Complex northwest of Pretoria - Von Gruenewaldt, G. (Gerhard), 1942- (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 1992.